Item Analysis of a Critical Thinking Skills Test on PLC Programming for Prospective Teachers - Rusimamto, Puput Wanarti; Munoto, Munoto; Samani, Muchlas; Anifah, Lilik (Jurnal Pendidikan Teknologi dan Kejuruan, 2019)
This study aimed at developing a test instrument to asses prospective vocational teachers’ critical thinking skills on Programmable Logic Controller (PLC) programming. This research and development study produced the test instrument that had been trialled to 68 Indonesian electrical engineering education prospective teachers at Universitas Negeri Surabaya. The method used was Research and Development by referring to the revised Bloom method and the adjusted Facione model. The instrument consisted of 40 items that were further analyzed using a classical test and item response approaches. Students' responses were analyzed using the computer program of a Test Analysis Program and ConQest. The item difficulty of classical test theory was represented by p value revealed based on prospective teachers’ correct answers. Parameter b referred to location parameter that conveyed the position of the item’s characteristic curve in relation to the ability scales. The benefit of this study was it can measure the level of critical skills, especially on the subject of PLC programming. The existing instruments only measure PLC programming skills in general but have not yet specifically reached the measurement of critical skills level.